2016
DOI: 10.4103/0976-7800.195694
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum 25-hydroxyvitamin D levels and bone mineral density in normal postmenopausal women

Abstract: Aim:This study was conducted with the objective of assessing serum 25-hydroxyvitamin D (25(OH)D) in postmenopausal women (PMW), to detect osteopenia or osteoporosis in PMW and to establish a correlation between serum 25(OH)D levels and bone mineral density (BMD).Materials and Methods:A total of 100 healthy PMW were selected, and a prospective observational study was conducted to correlate the BMD with serum 25(OH)D levels. Their laboratory investigations along with serum 25(OH)D levels were done. Their BMD was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…The serum level of 25(OH) vitamin D ( Fig. 1 ) was significantly lower in the Mets group, in accordance with the reports of increased cardiovascular risk associated with vitamin D deficiency ( 38 , 40 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The serum level of 25(OH) vitamin D ( Fig. 1 ) was significantly lower in the Mets group, in accordance with the reports of increased cardiovascular risk associated with vitamin D deficiency ( 38 , 40 ).…”
Section: Discussionsupporting
confidence: 90%
“…Among other markers, 25(OH) vitamin D may be considered by some specialised departments as a routine test for the differential diagnosis of osteoporosis ( 38 , 40 , 41 ). In our patients, we found very low levels of 25(OH) vitamin D, somehow confirming other reports; the median value was <30 ng/ml, which indicated that most of our subjects had inadequate serum 25(OH) vitamin D levels ( Table II ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced BMD, which is also known as osteopenia, may lead to osteoporosis and an increased risk of fracture if left untreated [48, 49]. Vitamin D deficiency is prevalent among patients with osteoporosis [50]. Supplementation with vitamin D and calcium has been shown to reduce the risk of hip fractures among elderly women [51].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies are equivocal, however, regarding the direct relationship between vitamin D and BMD [49, 50, 52, 53]. In addition, high levels of bone turnover markers in the blood may indicate increased bone loss [54].…”
Section: Discussionmentioning
confidence: 99%